Resistance and reconstruction of the image of ‘Self’ and ‘Other’: a passage to India and Things Fall Apart - Alam, Musrat (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2018.